METHOD OF MODELING IN PERFORMANCE TENNIS, THE MODERN SOURCE OF PERFECTING THE TRAINING CONCEPT (University Arena, 2025)
Performance tennis has made important progress in recent decade, both male and female, being illustrated by superior effort capabilities, dynamism in the technical-tactical actions of the game, power of concentration, quick recovery, adaptation to the diversified conditions of the game (time zone, weather conditions, opponents of different typologies). The laborious work of the coaches and the athletes are highlighted by somatic and  functional measurements, investigations and  scientific decisions of the teams of specialists.Sports performance in tennis knows in time a continuous process of modernization due to the valuable  interventions of the related sciences, which leads to a permanent redefinition of the principle of modeling and remodeling, on all the components that contribute to raising the human limits.The integrative (game and training) model includes the following components: the player's model or typology, the game parameters, the basic component model of the game. Modeling involves the reactivation of the specialized knowledge regarding the elaboration of valuable and performing training programs with maximum efficiency, without forcing the sportsman's body, modeling that must take into account the type of player (offensive, defensive, combinative) and a certain one technical, tactical and psychomotor strategy. Also, the modeling implies a good hierarchy of the criteria for evaluating the progress in preparation and in the game, conditioning and harmonization between the components of the training and the elements of effort and  recovery, hygiene and nutrition, adaptation and medication, motivation.We can state that once the game and training model is fixed, this activity can only be a stage, after which it will have to be improved by adding new modeling elements or by eliminating some that no longer correspond to the biological stages of the tennis players or require a series of adjustments that accelerate the improvement, according to the major requirements of higher level.